Outcomes of Physicians' Communication Goals During Patient Interactions. Issue 7 (7th June 2021) - Hua, Jacqueline; Howell, Jennifer L.; Sweeny, Kate; Andrews, Sara E.
ABSTRACT: During healthcare visits, physicians may set communication goals such as providing their patient with information about treatment; however, no recommendations exist regarding which goals physicians should prioritize during their often-brief interactions with patients. Two studies examined five communication goals (providing information, reducing distress, increasing patient satisfaction, increasing patient adherence, and encouraging hope) in the context of physician–patient interactions and their relationship with patient and physician outcomes. In Study 1, audio-recordings of physician–patient interactions were coded by research assistants for goal-related content. In Study 2, patients reported their physician's use of each goal during the interaction. In both studies, patients and physicians reported visit outcomes. Within-study meta-analyses suggested that the goal of reducing distress, but not the other goals, was consistently related to improved outcomes in Study 1. All goals were related to improved outcomes in Study 2. We then computed sample-size-weighted meta-analytic effects of each goal on each outcome across both studies. These results suggested that all of the goals had similar-sized positive relationships with patient and physician outcomes across studies. These findings suggest that physicians should generally approach consultations with communication goals in mind, but prioritizing efforts to reduce distress may be particularly beneficial.